The impact of physical activity on mental health - Myśliwiec, Natalia; Ciesielska, Aleksandra; Wojtczak, Marta; Sieradzka, Aleksandra; Kot, Alicja; Różycki, Adrian; Pniak, Michał; Mawlichanów, Maciej; Miklis, Paweł; Szerej, Krzysztof (Quality in Sport, 2025)
This article critically evaluates the interconnectedness of physical activity and mental health, drawing on a diverse body of evidence from observational studies, controlled trials, and emerging neuroscientific research. We explore how engaging in regular exercise is associated with improved mood regulation, reductions in anxiety and depressive symptoms, and better coping strategies under stress. By examining a range of exercise modalities, intensities, and durations across various age groups and demographic contexts, we shed light on the differential impacts of physical activity on mental well-being. Neuroscientific findings including those from neuroimaging and biomarker analyses offer insights into the biological mechanisms behind these improvements, revealing alterations in neural circuits and neurotransmitter systems that underpin emotional resilience and cognitive functioning. We further consider the psychological and social benefits that accompany regular physical activity, such as enhanced self-esteem, feelings of belonging, and the establishment of positive routines. Finally, we identify gaps in existing research, including the need for more tailored, evidence-based exercise prescriptions and an improved understanding of how to optimize interventions for individuals with specific mental health profiles. Overall, this review underscores the imperative of incorporating strategic physical activity programs into mental health prevention, treatment, and policy initiatives.